A Framework for Relevancy in Academic Departments - Ann Singleton; Michele Atkins (Academic Chairpersons Conference Proceedings, 2016)
Academic chairs lead the planning process for their departments. An important question for chairs becomes, “How can I develop and assess relevant goals?” This session offers participants a framework to establish a realistic understanding of how their academic departments relate to and are perceived by their outside and inside stakeholders.
Keywords: strategic planning; outcomes; departmental assessment; goal alignment; program evaluation; stakeholders